Pengembangan Media Pembelajaran Digital Berbasis Aplikasi Zep Quiz untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas V Sekolah Dasar - Nurlita Lestari; Liyana Sunanto (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to describe the results of a literature review on the use of digital learning media based on the Zep Quiz application in the learning process in elementary schools. This study was conducted to determine the feasibility, effectiveness, and attractiveness of Zep Quiz as an innovative and enjoyable digital learning medium. The method used was a Systematic Literature Review (SLR) by searching articles from Google Scholar using the keyword "Zep Quiz Application Development" for the period 2020-2025. From the selection results, four articles that met the criteria were obtained, which were then analyzed based on research findings and review results. The analysis showed that the use of Zep Quiz was highly feasible and effective in increasing student interest and learning outcomes. The application of gamification elements in this medium created an interactive, competitive, and enjoyable learning environment. Keywords: Digital learning media, Zep Quiz application, Changes in the state of matter, Learning interest Learning outcomes   Abstrak Penelitian ini bertujuan untuk mendeskripsikan hasil kajian literatur mengenai penggunaan media pembelajaran digital berbasis aplikasi zep quiz dalam proses pembelajaran di sekolah dasar. Kajian ini dilakukan untuk mengetahui tingkat kelayakan, efektivitas, dan daya Tarik zep quiz sebagai media pembelajaran digital yang inovatif dan menyenangkan. Metode yang digunakan adalah Systematic Literatur Review (SLR) dengan menelusuri artikel dari google scholar menggunakan kata kunci “Pengembangan Aplikasi Zep Quiz” pada rentang waktu 2020-2025. Dari hasil seleksi diperoleh 4 artikel yang memenuhi kriteria, kemudian dianalisis berdasarkan hasil penelitian dan hasil review. Hasil analisis menunjukkan bahwa penggunaan zep quiz dinyatakan sangat layak dan efektif dalam meningkatkan minat serta hasil belajar siswa. Penerapan elemen gamifikasi dalam media ini menciptakan suasana belajar yang interaktif, kompetitif, dan menyenangkan. Kata Kunci : Media pembelajaran digital, Aplikasi zep quiz, Perubahan wujud benda, Minat belajar, Hasil belajar.